1990
DOI: 10.1111/j.1365-3040.1990.tb02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Different stomatal responses of maize leaves after blue or red illumination under anoxia

Abstract: In normal air, illumination with a low level of blue or red light (40 μmol m−2 s−1) did not induce stomatal opening in maize plantlets. In CO2‐free air, 40 μmol m−2 s−1 of blue or red light promoted an enhancement in stomatal opening. At the same quantum flux, blue light was more efficient than red light and stomatal closure occurred more rapidly with a significantly shorter lag phase after blue light. Anoxia inhibited light‐dependent stomatal opening, even under 320 μmol m−2 s−1 illumination. However, after 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…It is important to note that the response by proton-pumping activity to oxygen levels is coincident with similar reductions in both photosynthetic and respiratory activities by GCPs exposed to the same oxygen concentrations (Mawson 1993). Thus, oxygen-dependency of proton pumping by GCPs shown here and for stomatal opening in intact tissue (Vavasseur et al 1990) possibly reflects the requirement for photo-and oxidative phosphorylation in order to support proton extrusion via a plasmalemma protonATPase. The sensitivity of BL-induced swelling to vanadate by V. faba GCPs is consistent with this proposal (Amodeo et al 1992).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is important to note that the response by proton-pumping activity to oxygen levels is coincident with similar reductions in both photosynthetic and respiratory activities by GCPs exposed to the same oxygen concentrations (Mawson 1993). Thus, oxygen-dependency of proton pumping by GCPs shown here and for stomatal opening in intact tissue (Vavasseur et al 1990) possibly reflects the requirement for photo-and oxidative phosphorylation in order to support proton extrusion via a plasmalemma protonATPase. The sensitivity of BL-induced swelling to vanadate by V. faba GCPs is consistent with this proposal (Amodeo et al 1992).…”
Section: Discussionmentioning
confidence: 85%
“…The failure of stomata to open when exposed to an atmosphere of low oxygen has been documented in several reports (Couchat et al 1988;Vavasseur et al 1990). It has been suggested that stomatal opening may be due to a mechanism of proton translocation involving a redox chain, in which oxygen would serve as a terminal electron acceptor (Raghavendra 1990;Gautier et al 1992).…”
Section: Discussionmentioning
confidence: 94%
“…Such comparisons indicate that differences in plant ionchannel kinetics may be species-dependent and highlight the need for comparative electrophysiological studies of cell types in other species, such as V. faba. The kinetics of changes in stomatal aperture are generally faster in grasses than in non-grass species (Raschke 1972;Rodriguez and Davies 1982;Johnsson et al 1976;Grantz and Zeiger 1986;Vavasseur et al 1988Vavasseur et al , 1990Karlsson et al 1990). In order to evaluate the implications of K § kinetics vis-a-vis rates of stomatal response in the intact leaf it will be necessary to obtain additional information on rates of membrane hyperpolarization and depolarization, since such voltage changes regulate both channel activation and the extent of associated ion flux.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is likely that BL creates a labile memory of a map of BL intensities on the plasma membrane. A transient memorization of BL signal has been demonstrated in stomatal guard cells (Vavasseur et al, 1990). This phenomenon could be explained by BL-induced phosphorylation of specific proteins (Chory, 1993).…”
Section: Transduction 1s Dependent On the Redox State Of The Cellmentioning
confidence: 99%